2018
DOI: 10.3136/fstr.24.609
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Nisin Combined with Plant-derived Antimicrobials on Pathogenic Bacteria and the Interaction with Complex Food Systems

Abstract: This study aimed to evaluate the synergistic effects of nisin combined with cinnamaldehyde (Nis+Cin) and nisin combined with carvacrol (Nis+Car) on food-borne bacteria. The minimum inhibitory concentrations for Nis, Cin and Car ranged from 2,500 to 10,000 IU/mL, 0.78-6.25 mg/mL and 0.78-3.13 mg/mL, respectively. Nis+Cin displayed a total synergism against all test bacteria, showing a marked release of bacterial intracellular constituents. In a food model, high protein concentration, low starch and oil concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Therefore, it was proposed that the ECPPE effectively inhibited the selected bacteria in a food matrix of high protein concentrations. These findings were in accordance with the efficacy of oregano and cinnamaldehyde against L. monocytogenes and S. typhimurium (Bouarab-Chibane, Forquet, et al, 2018) in high concentrations of the protein matrix, respectively, due to hydrophilic property of the beef extract solutions might interact electrostatically with the ECPPE to promote its dissolution in this medium (Klangpetch & Noma, 2018).…”
Section: Anti-bacterial Efficacy Of Ethanol Carica Papaya Peel Extrac...supporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, it was proposed that the ECPPE effectively inhibited the selected bacteria in a food matrix of high protein concentrations. These findings were in accordance with the efficacy of oregano and cinnamaldehyde against L. monocytogenes and S. typhimurium (Bouarab-Chibane, Forquet, et al, 2018) in high concentrations of the protein matrix, respectively, due to hydrophilic property of the beef extract solutions might interact electrostatically with the ECPPE to promote its dissolution in this medium (Klangpetch & Noma, 2018).…”
Section: Anti-bacterial Efficacy Of Ethanol Carica Papaya Peel Extrac...supporting
confidence: 83%
“…Of the tested bacteria, only V. vulnificus had growth inhibition > 100% significantly (p < 0.05) in the 70% palm oil solution. This finding suggested that the ECPPE could suppress the selected bacteria in a high concentration of fat system, which supported the inhibition of L. monocytogenes in sunflower oil concentrations by thyme and reduced lag time of S. typhimurium by cinnamaldehyde (Klangpetch & Noma, 2018). However, these findings contradicted the claim of the protective mechanism against bacteria by fat components and low water content in food from the anti-bacterial action of plant extract (Ma, 2015).…”
Section: Anti-bacterial Efficacy Of Ethanol Carica Papaya Peel Extrac...mentioning
confidence: 88%
See 1 more Smart Citation
“…The ingredient is part of the generally recognized as safe list of the U.S. Food and Drug Administration [10] and has been used as an efficacious antimicrobial against an array of pathogens, particularly Gram-positive bacteria in various concentrations, such as 5000 IU per gram of the products [11]. While an array of studies [12][13][14][15][16][17] are available investigating effects of nisin on enhancing the efficacy of thermal and nonthermal pasteurizations, there are limited studies to discuss the efficacy of this antimicrobial under elevated hydrostatic pressure and under precise control of temperature and intrinsic (e.g., water activity, nutrients, pH) and other extrinsic (e.g., relative humidity, presence of gases, activity and presence of competitor microorganisms) factors. This is primarily due to the fact that precision in controlling and monitoring the temperature of the pressure-based treatments has been a major challenge for academic and industrial high-pressure research in the last several decades [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Nisin is a peptide with antimicrobial properties that is produced by bacterium Lactococcus lactis and is the first bacteriocin approved for commercial utilization in food industry. Various concentrations of this chemical, including 1000 to > 5000 IU, have been studied as an antimicrobial agent against an array of microorganisms, particularly Gram-positive bacteria [ 18 , 19 , 20 , 21 , 22 , 23 ]. Caprylic acid (C8H16O2), found primarily in bovine milk, extracted palm and coconut oil, and carvacrol (C10H14O), found primarily in oregano, both belong to the GRAS list as well.…”
Section: Introductionmentioning
confidence: 99%